Analisis Leverage Melalui Pertumbuhan Laba dan Pengaruhnya terhadap Nilai Perusahaan - Arna Suryani (Universitas Batanghari, 2020)
This study aims to examine and analyze the effect of leverage though profit growth on firm value. Size of leverage is the rasio of debt to assets and debt to equity, and price book value is an indicator of firm value. The sample of this study was LQ45 companies listed on the Indonesia stock exchange which were selected based on certain criteria during the 2016 to 2018 observation period, and were selected as many as 34 companies so that the research sample was 102 observations. The analytical method is descriptive analysis using path analysis by testing four path structures. Normality and linearity were tested and F and t test the hypothesis.Based on result of the first path structure test leverage simultaneously and partially has no significant effect on profit growth. The result of the second path structure test simultaneously have a significant effect on firm value, and only partially the debt to equity ratio has a significant effect on firm value. The third path structure test that is profit growth directly has a significant effect on firm value, and the result of the fourth path structure test that is profit growth is considered capable of being a mediating link between leverage namely ratio of debt to asset (DAR) and debt to equity (DER) with price book value (firm value). These results prove that size of leverageis the ratio debt to asset and debt to equity can lead to increased profit growth, this is because profit growth is strongly influenced by management in carrying out company operations. Profit growth can also be a factor for investors or potential investors to value the company. Good news will be responded more quickly so that it will have an impact on the firm value.